Quelques propositions - Beaudoin, Gérald-A. (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
The rules of procedure in the House, the powers of the Speaker, the vote of non-confidence, the proportionnai representation vote as well as the future of parliamentary government, are some of the questions the author deals with when expounding upon the reform of the House of Commons. More powers should be given to the Speaker, and there should be a system where sessions and votes are held on a more regular basis, even if the principle of responsible government is maintained. The proportionnai representation vote is not for the immediate future and the author wonders whether a presidential system as in France would be appropriate for Canada.